Statistical optimization of conditions for protease production from Bacillus sp. - Saxena, Rajshree; Singh, Rajni (Acta Biologica Szegediensis, 2010)
Response surface methodology was employed for the optimization of different nutritional and physical parameters for the production of protease by a soil isolated Bacillus strain in submerged fermentation. Initial screening of production parameters as carbon (glucose) and nitrogen source (soybean) were optimized together with four variables K2HPO4, NaCl, MgSO4.7H2O, CaCl2.2H2O and four physical parameters including agitation, inoculum size, pH and time was performed using Plackett Burman design and the variables with statistically significant effect on the protease production identified. These variables were selected for further optimization studies using central composite design in RSM. The protease activity under unoptimized conditions was 330 U/ml. Under the final optimized conditions, the predicted response for protease production was 449 U/ml, and the observed validated experimental value was 577 U/ml. The statistical optimization by response surface methodology resulted in about two fold increase in the production of the enzyme by the selected bacterial strain.